(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
Starting from the notion of performativity in trans-feminist theories and Deleuze’s definition of institution as a “positive model for action”, it is possible to reposition the relationship between art and politics in the present time, with its shadows and ambiguities. Performing arts are defined as practices, human actions, counter-hegemonic narratives (hooks, 1998; Rancière, 2000); this paper investigates on the one hand the artistic processes based on the linguistic experimentation ​​and political imagination (Athanasiou, 2016). On the other hand, it gives an account of the political agency of art workers involved in processes of subjectivation and institutional practices (Ahmed, 2007), in multiple genealogies from the 1990s to today in Italy (Tpo, Teatro Valle Occupato, Macao, The Angel Mai). The critical analysis of the live arts provides a privileged observation point to read the transformations of contemporary work in the neoliberal framework - it is precisely the unproductive, performative “activity without work” that becomes the new paradigm of contemporary production (Virno, 2001).